THE EFFECT OF LEADERSHIP STYLE ON THE PERFORMANCE OF STATE CIVIL SERVICES AT THE OFFICE OF BAPPEDA PROVINCE PAPUA - Sindy Helena Rumparmpam; Andri Irawan; La Ode Marihi (Universitas Yapis Papua, 2022)
This study aims to determine the effect of Leadership Style consisting of Directiveness Leadership, Supportiveness Leadership, and Participate Leadership, which have the most dominant influence on the performance of state civil servants. . The sampling technique used is non-probability sampling with purposive sampling technique, with a total sample of `146 respondents. The analytical method used is multiple linear regression. The results showed that the directive leadership style, the supportive leadership style, and the participate leadership style had a positive and significant impact on the performance of state civil servants at the Bappeda Office of Papua Province. The leadership style of the director has a dominant influence on the Performance of State Civil Apparatus at the Bappeda Office of Papua Province